MODERN METHODS AND APPROACHES USED IN PROMOTING FOREIGN LANGUAGE LEARNING ("Conference on Universal Science Research 2023", 2023)
In this article, motivation is considered as one of the main factors determining the success of learning a foreign language. Different ways to increase motivation in a foreign language lesson are considered at school.